Energy efficiency and thermal performance of lightweight steel-framed (LSF) construction: A review - Soares, N. (2017)
The improvement of the use of renewable energy sources, such as solar thermal energy, and the reduction of energy demand during the several stages of buildings' life cycle is crucial towards a more sustainable built environment. This paper presents an overview of the main features of lightweight steel-framed (LSF) construction with cold-formed elements from the point of view of life cycle energy consumption. The main LSF systems are described and some strategies for reducing thermal bridges and for improving the thermal resistance of LSF envelope elements are presented. Several passive strategies for increasing the thermal storage capacity of LSF solutions are discussed and particular attention is devoted to the incorporation of phase change materials (PCMs). These materials can be used to improve indoor thermal comfort, to reduce the energy demand for air-conditioning and to take advantage of solar thermal energy. The importance of reliable dynamic and holistic simulation methodologies to assess the energy demand for heating and cooling during the operational phase of LSF buildings is also discussed. Finally, the life cycle assessment (LCA) and the environmental performance of LSF construction are reviewed to discuss the main contribution of this kind of construction towards more sustainable buildings.